Reviving the Competitive Storage Model : A Holistic Approach to Food Commodity Prices - Funke, Norbert (IMF Working Papers; Working Paper ;, 2011)
We revive in this paper the empirical relevance of the competitive storage model by taking a holistic approach to food commodity prices. We augment the seminal Deaton and Laroque (1992, 1996) model by incorporating more comprehensive and realistic supply and demand factors: output and demand trends, shocks to the yield, and time-varying interest rates. While the computational burden increases exponentially, the augmented model succeeds in replicating all four key patterns of food commodity prices. Our simulation and comparative statics also show that (i) the long-run declining trend of food prices may come to a halt or even reverse due to the shifting balance between supply and demand; (ii) short-run price fluctuations are mainly attributable to sizeable, though low-probability, shocks to output such as inclement weather; and (iii) the impact of monetary policy, though small in normal times, is nonlinear and asymmetric, and can become large if the real rate passes a certain threshold.